Triple- diffusive convection in a micropolar errofluid in the presence of rotation - Chand, Suresh (Zielona Góra: Uniwersytet Zielonogórski)
This paper deals with the theoretical investigation of the triple-diffusive convection in a micropolar ferrofluid layer heated and soluted below subjected to a transverse uniform magnetic field in the presence of uniform vertical rotation. For a flat fluid layer contained between two free boundaries, an exact solution is obtained. A linear stability analysis theory and normal mode analysis method have been employed to study the onset convection.
Keywords: triple- diffusive convection; micropolar ferrofluid; thermal convection; solute gradient; vertical magnetic field; rotation; magnetization